A Study on Tense Errors in the Compositions of Secondary Students in Brunei - Hazirah Daud (J-Lalite: Journal of English Studies, 2023)
This study examines the errors in tenses made by 34 secondary students in Brunei who were asked to write a short story based on a picture composition, with the focus on testing Krashen's Natural Order Hypothesis (NOH) in L2 acquisition. The objective of the study is to test the theory in NOH that irregular past tense is acquired before regular past tense through the analysis of the errors made in the verbs. The collected data were analyzed based on the four steps of error analysis: identification, description, explanation, and evaluation. The findings suggest that irregular past tense for verbs such as "go," "is," "eat," and "buy" were the most commonly found errors, mainly due to inappropriate or incorrect tense markings. Contrary to the hypothesis, the study suggests that irregular verbs are not necessarily acquired before regular past tense, possibly due to the large number of irregular verbs that learners need to know. Thus, the article concludes that the study provides useful information for language pedagogy and emphasizes the importance of considering the learners' L1 and individual differences in language acquisition.